Attainment Of Desired Magnetic Properties Of Mg-Zn Ferrite By Controlling The Composition And Microstucture - Tan, Thian Khoon (2000)
This research work was conducted to investigate and understand better the characteristics of magnesium based ferrites. Magnesium-based ferrites were chosen due to one of their vital characteristics, that is high electrical resistivity, which can make them better materials at higher operating frequencies. Besides, they have a lower production cost and no environmental effect. Therefore, perhaps, they can be a better substitute to the existing technological ferrites and consequently replacing them. In order to achieve these goals, a wide-scope experimental investigation was conducted . The samples were prepared by the oxide ceramic processing method, involving dry mixing and solid state reactions. The experimental investigation covered the effects of compositional variations in magnesium-based ferrites with iron deficiency, excess zinc, iron deficiency with excess zinc, magnesium-zinc ion exchange and magnesium-iron ion exchange. Additional experimental work was also carried out to study the effects, on microstructure, of the grinding time, pre-sintering temperature, sintering temperature and sintering time. It was found that, in general, iron deficiency and excess zinc was beneficial to obtaining good magnetic properties. For the magnesium-zinc and magnesium-iron ion exchange, there existed particular compositions which yielded optimum magnetic properties.